Virtue, Relationality, and the Self: Rethinking Love in Conversation with Autistic Moral Experiences - Agnew Cochran, Elizabeth (Journal of religious ethics, 2025)
Recent scholarship in religious ethics signals the importance of considering how the virtues are pursued and embodied in everyday human lives and practices, as well as attending to experiences of virtue that have previously been overlooked. This essay argues that experiences of love in autistic persons can enrich our understanding of the nature and scope of virtuous love as understood in the Christian tradition. In making this argument, I develop an account of autistic love that draws on scholarship from psychology and anthropology, first-person narratives published by autistic authors, and a qualitative study conducted at Duquesne University. These sources point toward the existence of a comprehensive and generalized love that is rooted in an understanding of oneself as profoundly interconnected with the surrounding world. I conclude this essay by considering how this sort of love, while not always explicitly Christian, can nevertheless inform two contemporary debates in Christian virtue ethics.